Scheming : a social history of Glasgow Council Housing, 1919-1956 - Damer, Seán (Edinburgh scholarship online., 2018)
Sean Damer provides a sustained critique of the Corporation of Glasgow's council housing policy and argues that it had the unintended consequence of amplifying social segregation and ghettoisation in the city.